Fractional flow reserve-guided complete vs. culprit-only revascularization in ST-elevation myocardial infarction patients with multivessel disease: a meta-analysis - Jingxian Yang; Jingxian Yang; Peng Wang; Jun Wan; Na Li; Jiajia Didi; Binger Shen; Xinyu Yang; Feina Li; Yu Zhang (Frontiers in Cardiovascular Medicine)
BackgroundAmong patients with ST-elevation myocardial infarction (STEMI) and multivessel disease, whether fractional flow reserve (FFR) guided complete revascularization (CR) is superior to the now widely used culprit-only (COR) revascularization is unclear.MethodsWe conducted a search of PubMed, Embase, the Cochrane Library, and CNKI for randomized controlled trials comparing FFR-guided CR with COR in STEMI patients with multivessel disease. Data extraction and analysis adhered to Cochrane guidelines, with major adverse cardiac events as the primary outcome.ResultsThis meta-analysis included 6 trials involving 3,482 patients. FFR-guided CR was associated with a reduction in major adverse cardiac events (RR: 0.66, 95% CI: 0.46–0.94, 95% PI: 0.20–2.19), ischemia-driven revascularization (RR: 0.27, 95% CI: 0.19–0.40, 95% PI: 0.16–0.46), and repeat percutaneous coronary interventions (RR: 0.35, 95% CI: 0.22–0.50, 95% PI: 0.16–0.78) compared to COR. However, no difference was observed in all-cause mortality (RR: 1.12, 95% CI: 0.86–1.46, 95% PI: 0.79–1.58) or safety outcomes.ConclusionFFR-guided CR reduces major adverse cardiac events compared to COR, though benefits may vary across settings. It significantly lowers ischemia-driven revascularization and repeat percutaneous coronary interventions, with no difference in all-cause mortality compared to COR.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024567524, PROSPERO (CRD42024567524).